Peruvian Chemistry Olympiad, twenty years promoting chemistry among youngsters - San Martín, Luis Ortega (2015)
The Peruvian Chemistry Olympiad celebrates its 20th anniversary and, in this report, a short review of the student participation in the event along with their origin and the international results obtained by each year’s winners is given.